2022
DOI: 10.3389/fpsyt.2022.1001336
|View full text |Cite
|
Sign up to set email alerts
|

Social media use and body image issues among adolescents in a vulnerable Louisiana community

Abstract: Widespread concern has been expressed regarding unrealistic body image and adolescent eating disorder promoting content on social media (SM) platforms. Numerous research studies have examined the impact of SM on body image as well as social vulnerability on negative mental health outcomes. Despite this, few previous studies have examined the impact of SM on body image specifically in vulnerable, underserved, or predominantly minority communities. This study examines the impact of SM on body image issues (BII) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 68 publications
0
15
0
2
Order By: Relevance
“…A study from Louisiana observed that females were more likely to use SM (p < 0.001) and report body image issues (p < 0.001) compared to males. However, body dissatisfaction corelated with increased time spent on SM across genders (p < 0.001) (39).…”
Section: Time Spent On Hvsmmentioning
confidence: 94%
“…A study from Louisiana observed that females were more likely to use SM (p < 0.001) and report body image issues (p < 0.001) compared to males. However, body dissatisfaction corelated with increased time spent on SM across genders (p < 0.001) (39).…”
Section: Time Spent On Hvsmmentioning
confidence: 94%
“…The MMMT (Hong et al, 2018) assessed six studies as moderate quality (Ferguson et al, 2014;Meier and Gray, 2014;Tiggemann and Slater, 2014;Brajdić Vuković et al, 2018;Mesce et al, 2022;Sagrera et al, 2022) and ten studies as strong quality (De Vries et al, 2014, 2016Ho et al, 2016;Kaewpradub et al, 2017;Chang et al, 2019;Boursier et al, 2020;Fardouly et al, 2020;Çimke and Yıldırım Gürkan, 2023;Digennaro and Iannaccone, 2023;Martinac Dorčić et al, 2023). Overall, the selected studies set out their research aims and methodologies clearly.…”
Section: Qualitative Assessmentmentioning
confidence: 99%
“…Sedangkan dari 7 responden yang mengakses media sosial lebih dari 15 jam per hari, 14,3% di antaranya memiliki citra tubuh yang rendah. Hal ini sejalan dengan hasil penelitian yang dilakukan di sebelumnya terhadap siswa sekolah menengah bahwa siswa yang menggunakan media sosial lebih dari 2 jam stiap hari memiliki peluang 1,59 kali lebih besar untuk mengalami isu citra tubuh dibandingkan dengan mereka yang menggunakan kurang dari 2 jam setiap hari [18]. Gambaran citra tubuh berdasarkan jenis media sosial dapat dilihat pada Tabel 5.…”
Section: Hasil Dan Pembahasanunclassified
“…Sedangkan pada hasil penelitian sebelumnya ditemukan bahwa YouTube, TikTok, dan Snapchat secara statistik menunjukkan pengaruh yang signifikan terhadap isu citra tubuh, di mana citra tubuh di dapatkan dari banyaknya postingan, tayangan yang terdapat pada berbagai media sosial tersebut, yang juga mempengaruhi pandangan masyarakat sekitarnya khususnya pada remaja [18]. Berbeda dengan hasil penelitian tersebut, kelompok responden yang mengakses Snapchat mayoritas memiliki citra tubuh pada kategori sedang (53,8%).…”
Section: Hasil Dan Pembahasanunclassified